EFEKTIVITAS BANK SAMPAH DALAM PENGELOLAAN SAMPAH KOMPREHENSIF MENUJU ZERO WASTE BERBASIS MASYARAKAT - Nur Azizah Affandy, Enik Isnaini (Prokons: Jurnal Teknik Sipil, 2016)
Application of 3R Activity in the community is still constrained mainly by a lack of public awareness for waste sorting. Based on the present issue of the problem of the environment, the Government of Lamonganhas Waste management policy through Lamongan Green and Clean program (LGC). This research used a descriptive approach. It aims to describe the phenomenon of waste management at the household level in Lamongan. In a descriptive research, there are two groups of data, namely quantitative and qualitative data. Thus, a qualitative descriptive research intended to determine the effectiveness of waste management through the LGC program at trash Bank in the village of Tumenggungan Lamongan District.The composition of rubbish in the village of Lamongan District consists of wet waste 63%, plastic 24%, paper 8%, and metal 5%. Effectiveness of waste management through waste bank starting from the sorting process. The process of waste sorting at the site of the township 54.9% stated that the process of waste segregation in housing did not bother. While nearly 71% do not bother. While the waste problem is most prevalent in the township of 64.8% of the respondents said that they had problems with rubbish. A total of  residential 33,33% of respondents in RT 03 RW 08 stated that they had problem with there is no time. For a time deposit garbage into a trash bank 90% of respondents in both the township and housing once a month.While the bank payment system in the residential trash 100% saving in the bank but more varied in township 87.3% Save it, 8,45% given the money directly and 5.63% exchanged for goods customers' needs. All respondents stated that they agreed with the trash bank in their environment. A total of 70.6% of all respondents were aware of the existence of trash bank and participating became customers of trash bank in their environment. 49.5% of respondents in the township have become customers of the waste bank for 3 years for bank category of waste has grown, while housing nearly 70% of respondents as a customer for one year for pioneering category of trash bank.Keywords: waste, LGC, 3R, waste bank